1993
DOI: 10.2135/cropsci1993.0011183x003300040030x
|View full text |Cite
|
Sign up to set email alerts
|

Irradiance and Nitrogen to Potassium Ratio Influences Sweetpotato Yield in Nutrient Film Technique

Abstract: Sweet potato [Ipomoea batatas (L.) Lam] is being grown with the nutrient film technique as part of the National Aeronautics and Space Administration's Controlled Ecological Life Support System (CELSS) program for long‐termed manned space missions. Our objective was to evaluated the effects of two levels of photosynthetic photon flux (480 and 960 μmols m−2s−1 PPF) and three N/K ratios (1:1.1, 1:2.4, and 1:3.6) on yield of sweetpotato when grown using this technique. Vine cuttings (15‐cm length) of ‘Georgia Jet’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…The decline in nutrient solution pH is striking but not unusual for potatoes in hydroponics. This phenomenon has been observed in a previous study (Chang et al, 2000), but not when the sole source of N is in the nitrate form (Mortley et al, 1993). The presence of N in the ammonium form indicates that potato plants are characterized by a high cation/anion uptake ratio resulting in an efflux of H + from roots, thus lowering solution pH (Marschner, 1995).…”
Section: Changes Of Ph and Ec And Nutrient Absorptionsupporting
confidence: 58%
“…The decline in nutrient solution pH is striking but not unusual for potatoes in hydroponics. This phenomenon has been observed in a previous study (Chang et al, 2000), but not when the sole source of N is in the nitrate form (Mortley et al, 1993). The presence of N in the ammonium form indicates that potato plants are characterized by a high cation/anion uptake ratio resulting in an efflux of H + from roots, thus lowering solution pH (Marschner, 1995).…”
Section: Changes Of Ph and Ec And Nutrient Absorptionsupporting
confidence: 58%
“…The nutrient solution pH was main-Research on growth responses of food crops under controlled environment conditions is being conducted by the National Aeronautics and Space Administration (NASA) through its Controlled Ecological Life Support Systems (CELSS) program for long-duration space missions. In ongoing studies Mortley et al, 1991aMortley et al, , 1991bMortley et al, , 1993 at Tuskegee Univ. 's NASA Center for Food Production, Processing, and Waste Management, we are evaluating hydroponic sweetpotato production using a nutrient film technique (NFT).…”
Section: Methodsmentioning
confidence: 99%
“…Bonsi et al (1992) grew sweetpotatoes under 24-h or 12h light periods in soilless culture and reported greater biomass production with continuous light compared with plants grown at 12-h light periods, which had fewer but larger leaves. Previous studies on the interaction of irradiance and N:K ratio on sweetpotato responses have shown that irradiance exerted a greater effect in increasing storage root yield than did N:K ratio (Mortley et al, 1993).…”
mentioning
confidence: 82%